Rosie's Pigeons - Azizian, Tamara (Auckland University of Technology, 2018)
This thesis consists of a full-length screenplay for a feature film. The Thesis is framed by an Exegesis, which is a 6000 word essay on the subject of: (a) The genre of the Thesis (b) The development process from synopsis to second draft
Keywords: Drama; Coming of age; Mystery; Crime